Complete bladder neck preservation promotes long-term post-prostatectomy continence without compromising midterm oncological outcome: analysis of a randomised controlled cohort - Nyarangi-Dix, Joanne; Tichy, Diana; Hatiboglu, Gencay; Pahernik, Sascha; Tosev, Georgi; Hohenfellner, Markus (World journal of urology, 2018)
The only RCT available on complete bladder neck preservation (cBNP) during radical prostatectomy reported superior continence and QoL outcomes in the first 12 months after cBNP. We provide the first data on long-term urinary continence, QoL and biochemical recurrence (BCR) after complete bladder neck preservation in a randomised controlled cohort.